ROLE OF VIDEO-EEG OF MONITORING IN DIAGNOSTIC EPILEPTIC AND NOT EPILEPTIC PAROXYSMAL STATES AT CHILDREN - V. I. Guzeva; O. V. Guzeva; V. V. Guzeva (Эпилепсия и пароксизмальные состояния, 2016)
The purpose of examination was revealing diagnostic efficiency of video-EEG monitoring for children with paroxysms. 259 children are included in examination in the age from 1 month till 18 years, from which 103 (39,8 %) girls and 156 (60,2 %) boys. All children are guided by neurologists to Centre of diagnostic and treatment of an epilepsy and nonepileptic paroxysmal disorders for refinement of the diagnosis, character paroxysmal derangement of consciousness, refinement of the shape of epilepsy, selection of adequate treatment. 80,69 % of children have acted with the diagnosis «epilepsy», 19,31 % of children – with the diagnosis nonepileptic paroxysms. Effects of complex diagnostic study in view of given video-EEG of monitoring have allowed to install an epilepsy of preferentially symptomatic character for 163 patients, and for 66 (40,49 %) patients install the partial form, for 16 (9,82 %) patients – generalized. For 68 (41,72%) patients there was a cryptogenic partial epilepsy, for 3 (1,84 %) patients – syndrome Landau-Kleffner and for 10 (6,14 %) patients – an idiopathic epilepsy. With the improved diagnosis nonepileptic paroxysms there were 96 patients. From them 44 (45,83 %) patients – with disturbance of a sleep (parasomnias), 21 (21,88 %) – with neurosolike states. Other nonepileptic paroxysms are installed for 26 (27,08 %) children, syndrome of a deficit of attention and hyperactivity – for 1 (1,05 %) the child.